A Dual Inhibitory Mechanism Sufficient to Maintain Cell-Cycle-Restricted CENP-A Assembly - Stankovic, Ana (2017)
Chromatin featuring the H3 variant CENP-A at the centromere is critical for its mitotic function and epigenetic maintenance. Assembly of centromeric chromatin is restricted to G1 phase through inhibitory action of Cdk1/2 kinases in other phases of the cell cycle. Here, we identify the two key targets sufficient to maintain cell-cycle control of CENP-A assembly. We uncovered a single phosphorylation site in the licensing factor M18BP1 and a cyclin A binding site in the CENP-A chaperone, HJURP, that mediated specific inhibitory phosphorylation. Simultaneous expression of mutant proteins lacking these residues results in complete uncoupling from the cell cycle. Consequently, CENP-A assembly is fully recapitulated under high Cdk activities, indistinguishable from G1 assembly. We find that Cdk-mediated inhibition is exerted by sequestering active factors away from the centromere. Finally, we show that displacement of M18BP1 from the centromere is critical for the assembly mechanism of CENP-A.